Small impact cratering processes produce distinctive charcoal assemblages - Losiak, Anna; Belcher, C. M.; Plado, J.; Jõeleht, A.; Herd, C. D. K.; Kofman, R. S.; Szokaluk, Monika; Szczuciński, Witold; Muszyński, Andrzej; Wild, E. M.; Baker, S. J. (My University, 2022)
The frequency of crater-producing asteroid impacts on Earth is not known. Of the predicted Holocene asteroid impact craters of <200 m diameter, only ~30% have been located. Until now there has been no way to distinguish them from “normal” terrestrial structures unless pieces of iron meteorites were found nearby. We show that the reflective properties of charcoal found in the proximal ejecta of small impact craters are distinct from those produced by wildfires. Impact-produced charcoals and wildfire charcoals must derive from different heating regimes. We suggest that charcoal with specific reflective properties may help to recognize the meteoritic origin of small craters.
Keywords: impact crater; crater; meteorite impact; ejecta; charcoal; Morasko; Kaali; Whitecourt; Poland; Estonia; Canada; wildefires; charcoal reflectivity; crater identification; asteroid impact; event deposits